Musical Learning and Teaching Conceptions as Sociocultural Productions in Classical, Flamenco, and Jazz Cultures. (October 2015) - Casas-Mas, Amalia; Pozo, Juan Ignacio; Scheuer, Nora
This study analyzes the discourse of musicians from three different cultures of musical learning, ranging from the more formal classical European culture, through the jazz culture, to the less formal flamenco culture in Roma communities. It is based on cultural studies of learning and education and the implicit conceptions theory. Thirty-one semi-professional guitarists were interviewed about learning and teaching music. We applied the lexicometrical method using correspondence analysis. We found significant lexical differences among the three cultures for all the three educational dimensions analyzed (teaching, learning, and evaluation). We describe literal answers from the most representative participants from each culture (using the automatic selection of modal response procedure according to χ 2 distance) and a qualitative analysis of their full answers. Finally, we project a distribution of the three cultures of learning onto a factorial plane, which summarizes distribution of the three cultures of learning according to two axes that we have interpreted in terms of (a) locus of control (self-others) and (b) phenomenology (analytical–emotional distance–conceptual–explicit knowledge/sensory–involvement–embodied–implicit knowledge), respectively. The discourse of classical and flamenco participants expressed other-regulated learning, although classical participants were closer to an explicit, conceptual pole, whereas flamenco participants were closer to an implicit, embodied pole. The discourse of jazz participants lay in between the other two, closer to the explicit pole, but including characteristic language about self-regulation.